Positioning of infraorbital foramen and mental foramen in orthognathic surgery：A CBCT study - CHEN Xin; TAO Cheng; WANG Tiemei (Kouqiang hemian waike zazhi)
[Objective] To determine the positions of the infraorbital foramen (IOF) relative to the anterior nasal spine (ANS) as well as the mental foramen (MF) relative to the pogonion (Pog), so as to provide reference for orthognathic surgery. [Methods] A total of 115 patients with cone‐beam CT (CBCT) images were randomly selected. We measured the distances and positional relationships between IOF and ANS, MF and Pog, using Mimics 15.0 software. [Results] On average, the ANS was 21.40 mm below the IOF and the horizontal distance between the IOF and ANS was 26.42 mm. The horizontal and vertical distances between MF and Pog was 23.57 mm and 9.71 mm, respectively. Scatter plots centered on ANS showed 83% (191/230) IOF appeared in a 30‐45° fan shape ranged in 30‐40 mm radius. 98% (226/230) MF occupied a 45° fan shape ranged in 20‐30 mm radius in bilateral superior quadrant centered on the Pog. [Conclusion] During the maxillary osteotomy, it exists a risk of injuring the infraorbital neurovascular bundle 21.40 mm above the ANS. To avoid IOF injury, excessive flap retraction should be avoided, especially below a 30° fan shape ranged in 30‐40 mm radius centered on ANS and a 45° fan shape ranged in 20‐30 mm radius centered on Pog. Special attention should be paid when performing flap elevation in this area.